Elevated Levels of Serum Fibrin and Fibrinogen Degradation Products Are Independent Predictors of Larger Coronary Plaques and Greater Plaque Necrotic Core - Corban, Michel T (Circ J, 2016)
BACKGROUND: Co-existence of vulnerable plaque and pro-thrombotic state may provoke acute coronary events. It was hypothesized that elevated serum levels of fibrin and fibrinogen degradation products (FDP) are associated with larger total plaque and necrotic core (NC) areas. METHODS AND RESULTS: Seventy-five patients presenting with stable anginal symptoms (69%) or stabilized acute coronary syndrome (ACS; 31%), and found to have non-obstructive coronary artery disease (CAD) with a fractional flow reserve >0.8, were studied. Invasive virtual histology intravascular ultrasound (VH-IVUS) was performed in 68 LAD arteries, 6 circumflex arteries, and 1 right coronary artery. Serum FDP levels were measured using ELISA technique. Plaque volumetrics and composition were assessed in each VH-IVUS frame and averaged. The median age of patients was 56 (47–63) years; 52% were men and 23% had diabetes. The average length of coronary artery studied was 62 mm. After adjustment for systemic risk factors, medications, CRP levels and ACS, male gender (P<0.001) and serum FDP levels (P=0.02) were independent predictors of a larger NC area. Older age (P<0.001), male gender (P<0.0001) and increased serum FDP level (P=0.03) were associated with a larger plaque area. CONCLUSIONS: In patients with CAD, a higher serum level of FDP is independently associated with larger plaques and greater plaque NC.